Pregnant women and COVID-19: isolation as a physical and psychic impact factor - Milene de Oliveira Almeida; Thainá Magalhães Portugal; Thais Josy Castro Freire de Assis (Instituto Materno Infantil de Pernambuco, 2020)
Abstract This research aims to reflect upon the inherent impacts of social isolation caused by the new coronavirus (COVID-19) pandemic on the health of pregnant women. It brings up a survey on both physical and psychological aspects of this period on a woman's life, such as physiological and emotional changes. It also raises questions about how these aspects can be directly or indirectly affected by periods of isolation, considering recent research and guidance from health reference organizations.